Getting a Haircut - Radabaugh, Melinda Beth. (Chicago, Ill. : Heinemann Library, 2003)
Describes what to expect on your first visit to the barber shop or salon for a haircut, discussing the big chairs, smocks, shampoo, haircutting tools, and blow-dryer.
Includes index.
Accelerated Reader AR
Keywords: Haircutting -- Juvenile literature